2001
DOI: 10.1103/physrevb.64.184426
|View full text |Cite
|
Sign up to set email alerts
|

Linewidth of single-photon transitions inMn12-acetate

Abstract: We use time-domain terahertz spectroscopy to measure the position and linewidth of single photon transitions in Mn12-acetate. This linewidth is compared to the linewidth measured in tunneling experiments. We conclude that local magnetic fields (due to dipole or hyperfine interactions) cannot be responsible for the observed linewidth, and suggest that the linewidth is due to variations in the anisotropy constants for different clusters. We also calculate a lower limit on the dipole field distribution that would… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

6
30
2

Year Published

2002
2002
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(38 citation statements)
references
References 22 publications
6
30
2
Order By: Relevance
“…cavity-less) high-field EPR, as compared to other techniques [16,26,28,29]. The zero field coherent time-domain THz technique employed by Parks et al [36], is limited in energy resolution (resolution is a fifth of the broadest EPR line width), as well as sensitivity. Consequently, it is necessary to study a large sample made up from unaligned microcrystals, and it is only possible to observe a few transitions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…cavity-less) high-field EPR, as compared to other techniques [16,26,28,29]. The zero field coherent time-domain THz technique employed by Parks et al [36], is limited in energy resolution (resolution is a fifth of the broadest EPR line width), as well as sensitivity. Consequently, it is necessary to study a large sample made up from unaligned microcrystals, and it is only possible to observe a few transitions.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, this technique leads to at least a three orders of magnitude improvement in detection sensitivity [28] relative to conventional single-pass multi-high-frequency EPR techniques [8,31,32,33,34,35,36], which opens up many new avenues for probing SMMs. To date, our single crystal investigations have focused primarily on the energy dependence of the positions in magnetic field of EPR absorptions corresponding to transitions between different spin quantum levels [26,27,28,29].…”
Section: Introductionmentioning
confidence: 99%
“…This picture, first established by magnetic measurements, 2 has been confirmed by the careful EPR study of spin levels in Mn 12 -acetate. [9][10][11][12][13][14][15] The EPR experiments have demonstrated noticeable resonant absorption of electromagnetic radiation by molecular magnets. Most recently, it has been suggested that a crystal of magnetic molecules can also be a powerful source of coherent microwave radiation.…”
Section: Introductionmentioning
confidence: 99%
“…Recent ESR experiments [17,18,19,20,21] have demonstrated noticeable resonant absorption of electromagnetic radiation by molecular magnets. In this Letter we show that crystals of magnetic molecules can also be a powerful source of coherent electromagnetic radiation.…”
mentioning
confidence: 99%
“…The lifetime of these states is believed to be dominated by spin-phonon processes [3,4] and by quantum spin tunneling [5,6,7,8]. The latter, for a field-sweep experiment, has been successfully described in terms of single-molecule Landau-Zener (LZ) transitions [9,10,11,12,13,14,15,16].Recent ESR experiments [17,18,19,20,21] have demonstrated noticeable resonant absorption of electromagnetic radiation by molecular magnets. In this Letter we show that crystals of magnetic molecules can also be a powerful source of coherent electromagnetic radiation.…”
mentioning
confidence: 99%